jtgg 2021
DOI: 10.20517/jtgg.2021.40
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and epileptic encephalopathies after negative or inconclusive genetic testing: what is next?

Abstract: The redefinition of classical electroclinical syndromes and the emergence of neurogenetics has led to a revolution in the field of developmental and epileptic encephalopathies (DEEs). In this context, advances in genetic techniques are leading to the final diagnosis of a large proportion of patients with DEE. However, up to 50% of patients with DEE remain undiagnosed. For patients with uncertain genetic etiology, there is a pressing need for the implementation of new targeted treatments and precision medicine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Our study identified molecular diagnosis in around 59% of participants, a yield higher than a range of 30% to 50% of DEEs attributed to a pathogenic variant [55,56]. As recently suggested, these results confirmed that the probability of reaching a correct diagnosis was enhanced by the methodological approach, particularly by in-depth phenotyping and the reanalysis of previous negative or uncertain sequencing data [18].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our study identified molecular diagnosis in around 59% of participants, a yield higher than a range of 30% to 50% of DEEs attributed to a pathogenic variant [55,56]. As recently suggested, these results confirmed that the probability of reaching a correct diagnosis was enhanced by the methodological approach, particularly by in-depth phenotyping and the reanalysis of previous negative or uncertain sequencing data [18].…”
Section: Discussionsupporting
confidence: 86%
“…All selected variants were confirmed, and segregation analysis was performed with Sanger sequencing. A reverse phenotyping strategy was used to refine the phenotype based on the interpretation of genetic data [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The true prevalence of DEEs is not well established, although it has been estimated that the overall annual incidence of monogenic epilepsies is around 1 per 2100 live births ( Symonds et al, 2019 ; Aledo-Serrano et al, 2021 ).…”
Section: Contrasts and Parallels Between Iges And Deesmentioning
confidence: 99%
“…If this primary diagnostic strategy is not conclusive ( 61 ), a reinterpretation of the pathogenicity of the detected variants (especially those variants of uncertain significance -VUS-) ( 62 ) and a reappraisal of the obtained results concerning the quality of the sequencing process (see the next section Considerations on Interpreting the Results of Genetic Testing) is warranted.…”
Section: Which Genetic Test To Performmentioning
confidence: 99%